Potential of Prebiotic Butyrogenic Fibers in Parkinson's Disease - Cantu-Jungles, Thaisa M.; Rasmussen, Heather E.; Hamaker, Bruce R. (Frontiers in Neurology, 2019)
Parkinson’s Disease (PD) is a neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra. Recent evidence supports the involvement of the gastrointestinal tract in PD pathogenesis, including alterations in microbiota and intestinal permeability. Apart from being the preferred energy source for colonic epithelial cells, butyrate is involved in anti-inflammatory, enteroendocrine and epigenetic mechanisms that influence colonic and systemic health, including brain function. A few studies using oral administration of sodium butyrate indicate beneficial effects in PD animal models, however prebiotic fibers that generate butyrate locally in the gut may be more effective. The design and selection of butyrogenic prebiotic fibers would allow preclinical studies to evaluate how gut-derived butyrate could affect PD pathophysiology. This review describes potential benefits of increasing gut butyrate production in PD through a prebiotic approach. Moreover, physico-chemical features of prebiotic fibers that target butyrogenic colonic bacteria are discussed.